2019
DOI: 10.21203/rs.2.17457/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

LncRNA HOTAIR regulates the expression of E-cadherin to affect nasopharyngeal carcinoma progression by recruiting histone methylase EZH2 to mediate H3K27 trimethylation

Abstract: Background In recent years, there has been increasing evidence for the function of long non-coding RNA (lncRNA) in nasopharyngeal carcinoma (NPC).. We aim to delve into the position of lncRNA HOTAIR, together with EZH2, E-cadherin and H3K27me3 in NPC and explore the related mechanisms. Methods RT-qPCR and western blot analysis were carried out for detecting lncRNA HOTAIR, EZH2, E-cadherin and H3K27me3 expression in NPC tissues and cells. Moreover, the correlations between lncRNA HOTAIR and EZH2 expression and … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 16 publications
(18 reference statements)
0
6
0
Order By: Relevance
“…E-cadherin, a typical epithelial cell marker, is a Ca 2+ dependent transmembrane glycoprotein closely related to intercellular adhesion. The dysregulation of E-cadherin expression that leads to carcinogenesis happens mostly at the epigenetic level (33,34). HDACs are enzymes mediating the removal of acetyl from lysine residues in either histones or other proteins, causing the repression of gene transcription and subsequent changes in signaling events (35), and HDAC1 was demonstrated to be involved in the transcriptional regulation of Ecadherin expression (17,18).…”
Section: Discussionmentioning
confidence: 99%
“…E-cadherin, a typical epithelial cell marker, is a Ca 2+ dependent transmembrane glycoprotein closely related to intercellular adhesion. The dysregulation of E-cadherin expression that leads to carcinogenesis happens mostly at the epigenetic level (33,34). HDACs are enzymes mediating the removal of acetyl from lysine residues in either histones or other proteins, causing the repression of gene transcription and subsequent changes in signaling events (35), and HDAC1 was demonstrated to be involved in the transcriptional regulation of Ecadherin expression (17,18).…”
Section: Discussionmentioning
confidence: 99%
“…After reading the full text, 18 studies were identified as eligible articles. According to the inclusion and exclusion criteria, 9 pieces of literature were eventually included in this study (26,(36)(37)(38)(42)(43)(44)(45)(46). All of the included studies were published between 2012 and 2021 with sample sizes between 44 and 425 patients and a total of 1,043 patients.…”
Section: Study Selection and Featuresmentioning
confidence: 99%
“…All of the included studies were published between 2012 and 2021 with sample sizes between 44 and 425 patients and a total of 1,043 patients. Seven studies with a total of 546 patients provided an association between the clinicopathological characteristics of HNSCC patients and HOTAIR expressions (26,(36)(37)(38)(43)(44)(45), and 6 studies with a total of 856 patients provided the correlation between HOTAIR expressions and HNSCC prognoses (26,36,38,42,45,46). Among the 9 studies, 7 studies were conducted in China, 1 in India (37), and 1 study involving survival outcomes was derived from the TCGA database (46).…”
Section: Study Selection and Featuresmentioning
confidence: 99%
See 2 more Smart Citations